Pengaruh Model Pembelajaran dan Motivasi Berprestasi Terhadap Hasil Belajar Sejarah di SMA Negeri 4 Karawang - Ikina Sabilillah (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
The aim of this research is to find the influence of a model of learning and achievement motivation to History Learning Outcomes in SMA Negeri 4 Karawang.This study is a kind of research quantitative with using the experiment design treatment by level 2x2. This research is quantitative which using experiment design treatment method by level 2x2.The population in this research are all the students in elevent grade,Sampel of research are XI IIS 2 and XI IIS 3 people a mount 60. The Instruments that used to the study the history learning outcomes is multiple choice and the instrument that used to know the result of achievement motivation is quisioner. The results of research refer to: (1) History learning outcomes that was giving STAD Learning Model is higher than was giving Direct Learning, (2) There is the influenanceimteraction between learning model and achievement motivation, (3) History learning outcomes that has achievement motivation and STAD Learning model is higher than was giving Direct learning model. (4) History learning outcome that has achievement motivation low and was giving STAD Learning model than was giving Direct Learning model.